Medidas de higiene en el salón de clases de 4 a 5 años en el Centro de Educación Inicial Planeta Azul en el Cantón Riobamba - Padilla Padilla, Estheffany Mishell (2025)
This research was carried out at the “Planeta Azul” Early Childhood Education Center in the city of Riobamba, in the province of Chimborazo. The main objective of this research is to encourage hygiene measures in the classroom through teaching resources that allow promoting the practice of cleanliness in children in initial II. The search for information was based on different reliable digital and bibliographic repositories such as: books, articles, magazines, among others. The research has a qualitative approach since it allowed a description of the study variables; The research was carried out with a sample of 30 children from initial II in the Planeta Azul Early Childhood Education Center. They were given an observation form that had 10 indicators with 5 items. During the research stage, it was observed that most children have good personal hygiene practices in terms of hand washing, face washing, and clothing hygiene. They also show interest in participating in activities related to personal hygiene and hygiene in school spaces. Therefore, it is considered important to encourage children to promote these habits since they are in a training process and need guidance and support from teachers and parents. Finally, five practical activities were proposed to work creatively with children in activities that promote personal hygiene with the youngest children. The activities were collected from other sources since it was considered important to rescue them to promote hygiene habits in the youngest children.